Influence of 3D printing system, postpolymerization and aging protocols on resin flexural strength and dimensional stability for printing occlusal splints, models and temporary restorations - de Gois Moreira, Fernanda Gurgel; da Silva, Nathalia Ramos; Bezerra, Marcella Guedes Pereira Gouvêa; da Silva, Sarah Emille Gomes; Butler, Sheila; Souza, Karina Barbosa [UNESP]; de Assunção e Souza, Rodrigo Othávio (Springer Nature, 2024)
Objectives: Investigate the effect of different postpolymerization protocols, aging, and 3D printing systems on the flexural strength (σ), dimensional stability, and roughness of resins used to fabricate occlusal splints, dental models, and temporary restorations. Material and methods: 180 bars (25 × 2 x 2 mm—ISO 4049) of each type of resin (T—Temporary/Cosmos Temp, Yller; OS—Occlusal splint/Cosmos Splint, Yller; MO – Models/ Cosmos Model, Yller) were printed and divided into 12 groups (n = 15) according to the factors: “Postpolymerization” (Ctr – Control; UV – Ultraviolet oven and MW – Microwave); “Printer” (SLA- stereolithography (Forms 2/Formslab); LCD- liquid crystal display (FlashForge Foto 6.0/FlashForge)) and “Aging” (TC – 10,000 thermocycling cycles and Without). Each bar was measured with a digital caliper at 11 points before and after postpolymerization to evaluate dimensional stability. The samples were subjected to the σ test (100Kgf;1 mm/min). Data was evaluated using Three- and Two-way ANOVA, and Tukey’s test (5%). Weibull analysis, Scanning Electron Microscopic and optical profilometry was performed. Results: LCD printing system and UV oven postpolymerization exhibited the highest σ (P <.05). The groups printed in SLA and post-polymerized in microwave ovens showed the greatest variations in their dimensions, for the occlusal splint resin, the OS-SLA-MW group (-4.29 ± 3.15)A showed a shrinkage of 40.2%. The resins for models (3.31 ± 0.66)A and temporary (-2.06 ± 1.52)A showed a shrinkage of 33% and 20.6%, respectively. Conclusions: LCD printing with UV light postpolymerization was the most effective method for resins used in occlusal splints, dental models, and temporary restorations. SLA printing with UV postpolymerization showed the most significant dimensional changes, leading to shrinkage in occlusal splint resins, while model resins and temporary restorations expanded. Clinical relevance: Resins for 3D printing should ideally be post-polymerized with UV light and printed using LCD technology, as this approach results in better mechanical properties and less dimensional change compared to microwave oven post-polymerization.
Keywords: Dental materials; Flexural strength; Models resin; Occlusal splits; Printing three-dimensional; Tooth crown